الحداثيون واستئناف القول بــ"خلق القرآن - حباسي, خالد (جامعة الوادي - University of Eloued, 2021)
الملخص: بما أن شبهة "خلق القرآن" هي من القضايا المشكلة في نقد الحداثيين للخطاب الشرعي الإسلامي، فسنذكر ملاحظات مهمة فيما يتعلق بتبنيهم لمقولة المعتزلة "القرآن كلام الله مخلوق"، التي استعاروها وجعلوها مدخلا لنقد القرآن الكريم، لأنه يحقق استراتيجيات النقدية التي تهدف إلى زحزحة الوحي عن المركز في النظام والوعي العقدي والفكري والعلمي في سياق راهننا الحضاري.ثم سنعمد إلى ذكر النتائج الحتمية لتبني هذه المقولة ، لنختم بذكر أوجه الفصل والمفارقة بين موقف المعتزلة وموقف الحداثيين من هذه الشبهة. Abstract Since the suspicion of "the creation of the Qur'an" is one of the problematic issues in the modernists' criticism of Islamic legal discourse, we will mention important remarks regarding their adoption of mu'tazila saying "The Qur'an is the word of Allah is created", which they borrowed and made as an entry point for criticism of the Holy Quran, because it achieves critical strategies that aim to displace the revelation About the center in the system and the doctrinal, intellectual and scientific awareness in the context of our civilizational present. Then we will mention the inevitable consequences of adopting this saying, to conclude by mentioning the separation and the paradox between the position of the mu'tazila and the position of the modernists of this suspicion.
مقال
Keywords: كلام الله مخلوق؛ المعتزلة، الحداثيون؛ نقد الخطاب الشرعي؛ تاريخية النص القرآني؛ النص والواقع; The Word of Allah is created; mu'tazila, hadith; criticism of the islamic discourse; the history of the Qur'anic text; the text and reality.